2021
DOI: 10.1126/science.abd9795
|View full text |Cite
|
Sign up to set email alerts
|

Reversible ketone hydrogenation and dehydrogenation for aqueous organic redox flow batteries

Abstract: Aqueous redox flow batteries with organic active materials offer an environmentally benign, tunable, and safe route to large-scale energy storage. Development has been limited to a small palette of organics that are aqueous soluble and tend to display the necessary redox reversibility within the water stability window. We show how molecular engineering of fluorenone enables the alcohol electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(127 citation statements)
references
References 43 publications
1
126
0
Order By: Relevance
“…In this study, the authors demonstrated an EE that ranged from 87% at 20 mA cm −2 to 48% at 80 mA cm −2 with good cycling stability for 500 cycles [159]. Feng et al [160] developed a ketone to be implemented as the active species in an A-ORFB by undergoing hydrogenation and dehydrogenation reactions. The fluorenone derivative that was produced showed efficient operation and stable long-term cycling.…”
Section: Organic Aqueousmentioning
confidence: 77%
“…In this study, the authors demonstrated an EE that ranged from 87% at 20 mA cm −2 to 48% at 80 mA cm −2 with good cycling stability for 500 cycles [159]. Feng et al [160] developed a ketone to be implemented as the active species in an A-ORFB by undergoing hydrogenation and dehydrogenation reactions. The fluorenone derivative that was produced showed efficient operation and stable long-term cycling.…”
Section: Organic Aqueousmentioning
confidence: 77%
“…In contrast, flow batteries are well suited for large-scale energy storage applications because they have high safety, high efficiency, and flexibility. 102 The vanadium flow battery, led by the Dalian Institute of Chemical Physics, Chinese Academy of Sciences, has been developed as one of the most mature technologies and is currently at the commercial demonstration stage. 103 Currently, the world's largest vanadium flow battery project (200 MW/800 MWh) is being built in Dalian, Liaoning.…”
Section: Technologies For Renewable Energymentioning
confidence: 99%
“…Several recent articles review the ever-broadening array of inorganic, organic, and organometallic active species under study for ARFBs. 1,2 Much research has focused on novel anolyte [3][4][5][6] or catholyte 7,8 development. Despite this progress, the community regularly notes the lack of suitable high-redox-potential catholytes, 9 with TEMPO, ferrocyanide, and ferrocene derivatives the most studied options that are functional at moderate pH.…”
Section: Introductionmentioning
confidence: 99%